Investigation model of sensing, seizing and reconfiguring capabilities - Carvalho; Lopes da Costa, R. (VI International Forum on Management – Familia y tecnología: Factores de resiliencia de las PYMEs durante la pandemia, 2022)
In the 90’s the Resource-Based View became the most prolific framework for value creation. Over time, markets revealed increasing levels of available technology and innovation, and the RBV was criticized for being too static and disregarding market dynamism. The Dynamic Capabilities View came to life as an enhancement of the RBV and became the most prolific research stream of the resource-based approaches. With most critics pinpointing definitional issues, contradictory interpretations, and tautological assumptions as issues to solve before the view could become a theory. Having these shortcomings in mind, the research aim of this investigation is to identify sensing and seizing capabilities, knowledge repositories to yield these capabilities, capabilities reconfigured that can be considered dynamic capabilities and finally which of these capabilities evolved through exploitation and exploration processes. This dissertation lays the foundations in the creation of a model which has the fundamental constructs of sensing, seizing and reconfiguring capabilities complemented by exploration and exploitation concepts, organizational ambidexterity constructs. To assess the applicability of this model, through a qualitative approach method, a set of semi-structured interviews took place to Portuguese managers. On a more operational manner the outcome of these interviews defined a set of capabilities companies should attempt to have to properly sense, seize and reconfigure to develop dynamic capabilities. The main contribution to the field of strategy is the suggestion of a link between the two constructs of sensing and seizing, and exploration and exploitation, further research will potentially strengthen this understanding.